A Remote Diet and Exercise Intervention for Surgical Patients With Prefrailty and Frailty During the COVID-19 Pandemic. Issue 2 (March 2023) - Desir, Marianne; Soberanes, Otmara; Tang, Fei; Garcia, Veronica M.
Objectives : To facilitate the success of surgical patients with prefrailty and frailty in meeting diet and exercise goals in the context of the COVID-19 pandemic, and to encourage patient satisfaction with remote care. Methods : In the setting of the COVID-19 pandemic, surgical patients with prefrailty and frailty were offered remote visits with a geriatrician and a remote diet and exercise coaching program. Results : The coaching participants set a mean of 37 (±15) individualized dietary goals and 17 (±11) individualized exercise goals. 75% of the coaching participants met at least 65% of their dietary goals and 75% met at least 50% of their exercise goals. All patients met at least one diet goal and at least one exercise goal. Patients endorsed high levels of satisfaction with the program. Discussion : Diet and exercise interventions for surgical patients with prefrailty and frailty have potential for adaptation to remote formats. Such interventions may facilitate patients' meeting of individualized diet and exercise goals and may also encourage patient satisfaction.